The Mechanism of Important Components in Canine Fecal Microbiota Transplantation - Kerong Li; Jie Yang; Xiaoxiao Zhou; Huan Wang; Yuxin Ren; Yunchuan Huang; Haifeng Liu; Zhijun Zhong; Guangneng Peng; Chengli Zheng; Ziyao Zhou (Veterinary Sciences, 2022)
Fecal microbiota transplantation (FMT) is a potential treatment for many intestinal diseases. In dogs, FMT has been shown to have positive regulation effects in treating Clostridioides difficile infection (CDI), inflammatory bowel disease (IBD), canine parvovirus (CPV) enteritis, acute diarrhea (AD), and acute hemorrhagic diarrhea syndrome (AHDS). FMT involves transplanting the functional components of a donor’s feces into the gastrointestinal tract of the recipient. The effective components of FMT not only include commensal bacteria, but also include viruses, fungi, bacterial metabolites, and immunoglobulin A (IgA) from the donor feces. By affecting microbiota and regulating host immunity, these components can help the recipient to restore their microbial community, improve their intestinal barrier, and induce anti-inflammation in their intestines, thereby affecting the development of diseases. In addition to the above components, mucin proteins and intestinal epithelial cells (IECs) may be functional ingredients in FMT as well. In addition to the abovementioned indications, FMT is also thought to be useful in treating some other diseases in dogs. Consequently, when preparing FMT fecal material, it is important to preserve the functional components involved. Meanwhile, appropriate fecal material delivery methods should be chosen according to the mechanisms these components act by in FMT.